An exhaustive overview of floating drug delivery system - Mukherjee, Lucky; Chandra, Srikanta; Mukherjee, Bijayan; Bhowmick, Mithun (Journal of Drug Delivery and Therapeutics, 2019)
The purpose of writing this review is to narrowing down on floating drug delivery systems (FDDS) and to compile the current literature with special focus on the principal mechanism of floatation to ameliorate gastric retention. The current amelioration of FDDS including the physiological and formulation variables affecting gastric retention approaches to design single unit and multiple unit floating systems, and a plethora and formulation aspects are covered in detail. This review also summarizes the in vitro technique and in vivo studies to evaluate the performance and application of floating systems and applications of these systems. These systems are useful to several plights encountered during the amelioration of a pharmaceutical dosage form.Keywords:  FDDS: Floating Drug Delivery System, ND: Narrowing down, PD: Pharmaceutical dosage